2007
DOI: 10.1016/j.chembiol.2007.09.010
|View full text |Cite
|
Sign up to set email alerts
|

CD1c Presentation of Synthetic Glycolipid Antigens with Foreign Alkyl Branching Motifs

Abstract: Human CD1c is a protein that activates alphabeta T cells by presenting self antigens, synthetic mannosyl phosphodolichols, and mycobacterial mannosyl phosphopolyketides. To determine which molecular features of antigen structure confer a T cell response, we measured activation by structurally divergent Mycobacterium tuberculosis mannosyl-beta1-phosphomycoketides and synthetic analogs with either stereorandom or stereospecific methyl branching patterns. T cell responses required both a phosphate and a beta-link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
65
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 74 publications
0
65
0
Order By: Relevance
“…For example, the alkyl chains of Mtb diacylated sulfoglycolipids (AC 2 SGL) govern CD1b-mediated T cell activity, including Cmethyl substituents, stereochemistry and alkyl chain position (39). T cell activation is also sensitive to alkyl chain differences in the CD1c-antigen mannosyl-β-phosphomycoketide (MPM), with length, methyl branching pattern and stereoarrangments influencing responses (40). Furthermore, the length of the alkyl chains and lipid saturation of the CD1d-antigen α-galactosylceramide (α-GalCer) is important for controlling CD1d-restricted invariant NKT cell activity (41).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the alkyl chains of Mtb diacylated sulfoglycolipids (AC 2 SGL) govern CD1b-mediated T cell activity, including Cmethyl substituents, stereochemistry and alkyl chain position (39). T cell activation is also sensitive to alkyl chain differences in the CD1c-antigen mannosyl-β-phosphomycoketide (MPM), with length, methyl branching pattern and stereoarrangments influencing responses (40). Furthermore, the length of the alkyl chains and lipid saturation of the CD1d-antigen α-galactosylceramide (α-GalCer) is important for controlling CD1d-restricted invariant NKT cell activity (41).…”
Section: Discussionmentioning
confidence: 99%
“…The polar heads of these antigens vary in size from the small carboxylic group of MA to the pentasaccharide of GM1 or potentially larger structures in lipoarabinomannans. Hydrophobic tails, which decisively govern CD1-restricted presentation of some antigens (16,17), also greatly differ in length and structural complexity. For example, up to C 80 long tails, which are not trimmed before presentation (18), compose MA and GMM, whereas short 18:1/16:0 tails are found in GM1.…”
mentioning
confidence: 99%
“…, glucose monomycolate (GMM) (7), glycerol monomycolate (GroMM) (8), diacylated sulfoglycolipids (Ac 2 SGL) (9), mannosyl-␤-1-phosphomycoketide (MPM) (10,11), lipoglycans (lipoarabinomannan and lipomannan) (12), and lipopeptides (13).…”
mentioning
confidence: 99%
“…Synthetic MPM analogs were prepared, incorporating polyprenyl chains where the length and absolute configurations of the C-methyl-branched carbons had been modified and used to stimulate specific T cells. It was concluded that the length, the methyl branching pattern, and the stereochemistry of the polyketide chain control the T cells response (11). Whether this effect was related to differences in lipid intracellular trafficking, CD1c loading, TCR recognition, or a combination of these biological aspects is still not fully understood.…”
mentioning
confidence: 99%